Synthesis, in vitro aerobic and hypoxic cytotoxicity and radiosensitizing activity of novel metronidazole tethered 5-fluorouracil - Abdi, Khosrou (BioMed Central, 2013)
BACKGROUND AND THE PURPOSE OF THE STUDY: Several 2, 4-dinitrophenyl and 2,4-dinitrophenylamine tethered 5-FU (5-fluorouracil) compared to their components have shown minimal or no cytotoxicity to HT-29 cell line under aerobic conditions but high cytotoxicity and radiosensitizing effects under hypoxic conditions. In the present study the cytotoxicity and radiation potentiation of three novel analogues of these compounds by replacing 2,4-dinitrophenyl moiety with 2-methyl-5-nitroimidazole, a known radiosensitizer and cytotoxic agent was investigated. METHODS: Tethered compounds 7–9 were prepared by the reaction of 1-(t-butoxycarbonyl)-5-fluorouracil 6 with metronidazole esters 2–4 followed by removal of the t-butoxycarbonyl protecting group. Cytotoxicity of compounds in HT-29 cells with or without radiation were determined by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), propidium iodide (PI)-digitonin and clonogenic assays. RESULTS: Tethered compounds 7–9 induced time-and concentration–dependent cytotoxicity under hypoxia but had no significant effect under aerobic conditions. These compounds also showed selective and concentration- dependent radiosensitization effects under hypoxic conditions. CONCLUSION: Tethered compounds 7–9 compared to 5-FU 5 showed minimal cytotoxicities under aerobic and selective radiosensitizing activities under hypoxic conditions. Also effects of these compounds were higher than those of metronidazole 1 which is a known cytotoxin and radiosensitizer under hypoxic conditions.